16th AIAA Aviation Technology, Integration, and Operations Conference 2016
DOI: 10.2514/6.2016-3161
|View full text |Cite
|
Sign up to set email alerts
|

Operational Characteristics Identification and Simulation Model Verification for Incheon International Airport

Abstract: Incheon International Airport (ICN) is one of the hub airports in East Asia. Airport operations at ICN have been growing more than 5% per year in the past five years. According to the current airport expansion plan, a new passenger terminal will be added and the current cargo ramp will be expanded in 2018. This expansion project will bring 77 new stands without adding a new runway to the airport. Due to such continuous growth in airport operations and future expansion of the ramps, it will be highly likely tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
6
0
1

Year Published

2017
2017
2020
2020

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 5 publications
4
6
0
1
Order By: Relevance
“…Figure 10 shows the three-dimensional contour plot of the dependencies of the throughput Q on the distribution probability a and the interval of arrival time T in . It was observed that throughput Q gets sluggish and reaches the plateau as T in increases, thus making a type of sigmoid curve, the tendency of which is similar to the experimental data of the same type of systems in previously reported works [25][26][27]. On the other hand, the dependence of throughput Q on arrival time interval T in does not reach the plateau in between 4 and 2min at around where the parameter α gets close to the ratio of the number of parking sites in the domestic route to that in the whole system.…”
Section: Analysis With the Classical M M C Queuesupporting
confidence: 85%
See 1 more Smart Citation
“…Figure 10 shows the three-dimensional contour plot of the dependencies of the throughput Q on the distribution probability a and the interval of arrival time T in . It was observed that throughput Q gets sluggish and reaches the plateau as T in increases, thus making a type of sigmoid curve, the tendency of which is similar to the experimental data of the same type of systems in previously reported works [25][26][27]. On the other hand, the dependence of throughput Q on arrival time interval T in does not reach the plateau in between 4 and 2min at around where the parameter α gets close to the ratio of the number of parking sites in the domestic route to that in the whole system.…”
Section: Analysis With the Classical M M C Queuesupporting
confidence: 85%
“…In the case of 2 min, an important observation was made; the throughput Q reduces after α reaches the maximum capacity. The overall reduction of throughput Q in between 0.6 and 1.0 seems to be unique because the throughput plateaus after saturation, in similar systems [25][26][27]. Besides, we confirmed from figure 5 that the existence of the delay of staying time is not the critical factor for the overall reduction because we observe it in both cases: with stochastic and with deterministic parameters.…”
Section: Simulation Resultssupporting
confidence: 65%
“…Airport surface traffic optimization for ICN has been studied with the requirements and the relevant assumptions defined based on the airport operational characteristics [3]. For the surface traffic optimization, the three-step approach [7][8][9][10] was applied, which consists of;…”
Section: B Optimization Based Approachmentioning
confidence: 99%
“…Inha University, a member of the consortium, is developing a scheduler based on a First-Come First-Served (FCFS) approach [1,2]. KARI is developing a scheduler using MILP through collaborative research with NASA [3,4].…”
Section: Introductionmentioning
confidence: 99%
“…국내의 경우, 국토교통부의 '항공기 출발 도착 통합 관리 연구'를 통해 포화 상태에 다다른 국내 공항들의 교통 관 리 기능의 향상을 기대하고 있다 [2]. 본 논문은 기존 연구를 기 반으로 [3][4][5], 일반화된 노드-링크 (node-link) 모델에서의 선입-선처리 알고리즘 (FCFS; first-come first-served algorithm)을 이 용한 항공기 지상 이동 스케줄링 기법에 대해 설명한다.…”
unclassified